Medical student education in transfusion medicine, part II: Moving forward to building up a "Know How" education program in transfusion medicine for under-graduate medical students. (December 2020) - Garraud, Olivier; Vuk, Tomislav; Brand, Anneke; de Angelis, Vincenzo; Politis, Constantina; Haddad, Antoine; Vlaar, Alexander P.J.; Lozano, Miquel; Ertuğrul Örüç, Nigar; Laspina, Stefan; Tissot, Jean-Daniel
Abstract: There is a general trend in changing paradigm in teaching medicine; the emerging concept relies on a competence-based approach. Transfusion is either a discipline or a subsidiary of others depending on the countries and systems; this variability can be explained because transfusion is a medical care that is transdisciplinary. As a collective of professionals in both transfusion medicine practice and education, authors aim to propose a revision of the way education in transfusion medicine is delivered in this era of the 'global competency approach'. They advocate in favor of a Know How on 5 key issues: Diagnosing the patient condition in line with the Patient Blood Management principles; Facing acute blood loss; Addressing compatibility and avoiding immunization; Seeking for maximized benefits and dampening complications; and Inlaying competence within global health care issues, also comprising od economy. The methods used would be those developed for medical education at large, such as assessment tools. The global objective is to deliver the necessary competence to manage patients by an intern/resident. At the end of the curriculum, students should be able to self-evaluate the following items: 1) Do I know why my patient is anemic, thrombocytopenic, bleeding….? 2) Do I know the best approach to treat anemia, thrombocytopenia, bleeding (including the "no treatment" option)? 3) Do I know whether a transfusion approach is appropriate for my patients? 4) Do I know how to evaluate and anticipate benefits from blood transfusion and to avoid side-effects in the patient? 5) Do I know how to avoid unnecessary use of the products?